THE IDEA OF A PERFECT MAN IN THE TEACHINGS OF MEDIEVAL EASTERN RENAISSANCE THINKERS - Shukurullo Rayimov (Web of Journals Publishing, 2024)
This article focuses on the ideas of the Renaissance period, in which it is noted that it is possible to direct people to happiness through the system of power, to coordinate the relations between society and the state with the help of science and good morals.
Keywords: Creative idea, society, state, perfect person, thoughts of Farabi and Amir Temur.